Analytical and experimental study of wave setup over permeable coral reef. (September 2019) - Zhu, Gancheng; Ren, Bing; Wen, Hongjie; Wang, Yongxue; Wang, Chao
Abstract: An analytical solution is proposed to predict the wave set-up over permeable reef flat based on porous flow model and momentum conservation. A laboratory experiment is carried out to verify the analytical solution. Good agreement is obtained by comparing the analytical results and the experimental data. Both the analytical results and the experimental data show the wave setup increases with the increase of the incident wave height and the decrease of the submergence water depth. The influences of the porous properties of the coral reef on wave set-up are discussed based on the analytical solution and experiment results. The wave set-up on the reef flat is found to decrease with the increasing particle size of porous media layer. The increase of the porosity and the height of porous media layer can lead to significant reduction in the wave set-up on the reef flat.